2017
DOI: 10.1371/journal.pone.0187065
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin in morbidly obese women with non-alcoholic fatty liver disease

Abstract: BackgroundNon-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in Western countries. Both iron and lipid metabolism seem to be involved in its pathogenesis. We aimed to assess the relationship between levels of hepcidin, the master iron-regulatory protein, in plasma and the presence of NAFLD in morbidly obese (MO) patients, and to investigate the association between the hepatic expression of the main iron and lipid metabolism -related genes.Materials and methodsEnzyme-lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 54 publications
(70 reference statements)
3
23
0
Order By: Relevance
“…The increase in hepcidin we observed is consistent with previous studies in models with chronic inflammation such as obese mice 44 . This finding is supported by previous research indicating that in morbidity obese women with non-alcoholic fatty liver disease, the hepatic mRNA expressions of hepcidin and FPN were significantly greater than in obese women with normal liver 45 . Although FPN inactivation by hepcidin results in displacement from the cellular membrane into the cytosol 46 , the activity of FPN may not coincide with the amount of FPN.…”
Section: Discussionsupporting
confidence: 88%
“…The increase in hepcidin we observed is consistent with previous studies in models with chronic inflammation such as obese mice 44 . This finding is supported by previous research indicating that in morbidity obese women with non-alcoholic fatty liver disease, the hepatic mRNA expressions of hepcidin and FPN were significantly greater than in obese women with normal liver 45 . Although FPN inactivation by hepcidin results in displacement from the cellular membrane into the cytosol 46 , the activity of FPN may not coincide with the amount of FPN.…”
Section: Discussionsupporting
confidence: 88%
“…DOI: 10.1159/000497228 ies have reported a relationship between serum ferritin and NAFLD, the connection was still disputable [11,12,14]. In the present study, we found that patients with NAFLD had higher serum ferritin levels than control subjects, and an elevated level of serum ferritin was associated with a significantly increased risk of NAFLD (OR = 1.679, 95% CI 1.189-2.371).…”
Section: Discussion/conclusionmentioning
confidence: 40%
“…Several human studies have elucidated the role of hepcidin in iron overload and chronic liver disease [21,22], but its effect on NAFLD is controversial. In the study by Auguet et al [11], the plasma levels of hepcidin among women with morbidly obesity were not significantly different between NAFLD patients and those with normal liver; however, Demircioğlu et al [16] reported that among children with obesity, hepcidin levels were significantly higher in NAFLD patients than in controls. In the present study, we found that serum hepcidin levels were not associated with NAFLD risk, but may have augmented the risk effect of central obesity on NAFLD (p = 0.04).…”
Section: Discussion/conclusionmentioning
confidence: 92%
See 2 more Smart Citations